Developing definitions of conventional hardness tests for use by National Metrology Institutes. (December 2021) - Low, S.; Germak, A.; Knott, A.; Machado, R.; Song, J.
Abstract: This paper describes the process used by the Consultative Committee for Mass and Related Quantities - Working Group on Hardness (CCM-WGH) of the International Committee of Weights and Measures (CIPM) to develop international definitions of the conventional Rockwell, Brinell, Vickers and Knoop hardness test methods, for use by the National Metrology Institutes (NMI) that standardize hardness measurement.